An investigation into the effect of water injection parameters on synergetic mining of geothermal energy in mines. (1st January 2023) - Xu, Yu; Li, Zijun; Tao, Ming; Jalilinasrabady, Saeid; Wang, Junjian; Li, Gang; Zhong, Kaiqi
Abstract: Cooling energy demands are high and increase with the mining depths in conventional mine cooling systems, which account for the most of the total energy consumption. The synergetic mining of mine geothermal energy (SMGE) is a subversive and promising approach for heat hazard control of deep mines with the advantage of low energy consumption and low cost. In this study, the similarity criteria for the similar simulation of SMGE are deduced by the equation analysis method, and the similarity criteria number between the full-scale model and the reduced-scale model is determined. Based on the geometric scale ratio of 1:100, a simulation experiment system including ventilation system and geothermal exploitation system is established. In addition, the influence of water injection parameters on cooling effect of roadway and heat recovery performance of the SMGE system is investigated. The results indicate that the temperature of surrounding rock is cooled gradually during the water injection and heat recovery in rock formation, which reduces the temperature increase rate of airflow in the roadway. When the injection water temperature is reduced from 28 °C to 11.5 °C, the cooling rate of roadway can be observable increased, but it results in a faster temperature decrease in production water with time. Increasing the water injection time from 35 min to 65 min will give rise to the temperature reduction degree of surrounding rock and decrease to the temperature increase rate of airflow in roadway. And the time of water injection is directly proportional to the water production flow rate in production well, but inversely proportional to the temperature in production water. A high injection rate facilitates the cooling rate of the roadway and increases the range of heat recovery in formation, but a small flow rate can achieve a better ultimately cooling effect under the same total water injection volume. Decreasing the water injection rate from 1.6 L/min to 0.6 L/min will increase the time of stable production flow and the rate of reduce in water temperature in the production well. Furthermore, changes in the level of the injection well position will result in different injected water seepage characteristics, which affects the cooling effect of roadway and heat recovery performance of the SMGE system simultaneously. Highlights: The similarity criteria for the similar simulation of SMGE are deduced. A simulation experiment system with a geometric scale ratio of 1:100 is established. Several scenarios of similar experiment for SMGE are carried out. The cooling effect and heat recovery performance are analyzed.